2020
DOI: 10.1007/s11157-020-09556-8
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in microalgae-based treatment of high-strength wastewaters: challenges and opportunities to enhance wastewater treatment performance

Abstract: Microalgae-based technologies, usually configured as high rate algal ponds (HRAP), are efficient, sustainable, and cost-effective alternatives for wastewater treatment due to their high removal efficiencies at low energy demand, ability to recover nutrients and ease of operation. HRAPs and other photobioreactors have been intensively studied in recent years for the treatment of highstrength wastewaters, which are mainly characterised by high and unbalanced (in terms of microalgae requirements) concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 189 publications
(231 reference statements)
0
18
0
4
Order By: Relevance
“…Experimental data from the demonstration‐scale system were used to determine food waste fed to the anaerobic reactor and the microalgal biomass produced in the HRAP (Table 5). 32,56 According to literature, HRAPs have been used for treating diverse sorts of anaerobic supernatants, such as domestic sewage, animal manure, agricultural wastes, and food waste, among others 57 . Research has shown that, since food waste supernatants have a high concentration of organic matter, ammonia, and solids, its low C/N ratio, high N/P ratio, and high turbidity may hinder microalgae growth 57,58 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental data from the demonstration‐scale system were used to determine food waste fed to the anaerobic reactor and the microalgal biomass produced in the HRAP (Table 5). 32,56 According to literature, HRAPs have been used for treating diverse sorts of anaerobic supernatants, such as domestic sewage, animal manure, agricultural wastes, and food waste, among others 57 . Research has shown that, since food waste supernatants have a high concentration of organic matter, ammonia, and solids, its low C/N ratio, high N/P ratio, and high turbidity may hinder microalgae growth 57,58 …”
Section: Resultsmentioning
confidence: 99%
“…32,56 According to literature, HRAPs have been used for treating diverse sorts of anaerobic supernatants, such as domestic sewage, animal manure, agricultural wastes, and food waste, among others. 57 Research has shown that, since food waste supernatants have a high concentration of organic matter, ammonia, and solids, its low C/N ratio, high N/P ratio, and high turbidity may hinder microalgae growth. 57,58 Based on the results obtained in this scenario, a proportion of 99:1 (%VS FW :%VS MA ) of food waste and microalgal biomass would be fed to the anaerobic reactor, if all the microalgae produced with the current food waste fed to the digester were considered.…”
Section: Co-digestion Of Total Microalgal Biomass Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a preference to use the appropriate wastewater effluents to obtain efficient nutrient uptake and remove the barriers in the way of microalgae-based wastewater treatment. 206…”
Section: Phycoremediation: Wastewater Treatment Using Microalgaementioning
confidence: 99%
“…By providing oxygen to nitrifiers, algae substantially increase the overall ammonium removal capacity of the system, while nitrifiers reduce the oxygen level below the inhibition thresholds for algae . Nitrification, in turn, helps by keeping the ammonium concentration low, thus reducing the risk of free ammonia inhibition on algae, especially when high strength wastewaters are to be treated. , Nitrifiers convert ammonium into nitrate that can be uptaken by the algae. The combination between algae and nitrifying bacteria has also some drawbacks, inducing negative interactions like the competition for CO 2 or micronutrients or the inhibition of bacterial growth when the photosynthesis increases the pH level .…”
Section: Introductionmentioning
confidence: 99%